1994
DOI: 10.1037/1196-1961.48.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Turning selective attention failure into selective attention success.

Abstract: In a letter identification task in which a centrallypresented letter is to be attended and laterally-flanking letters ignored, B.A. Eriksen and C.W. Eriksen (1974) have shown effects on performance of the to-be-ignored letters when they contain information about the correct response. These data constitute important evidence of late selection for attention on condition that the flankers are not, in fact, attended. Three experiments assess the importance of (1) practice on the task; (2) positional uncertainty re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…The contextual cueing paradigm (Chun and Jiang, 1998; 1999) leads to improved task performance because the distractors actually guide attention, rather than being filtered (though see Makovski, et al (2008), for an example of learning restricted to the target items). Brown and Fera (1994) showed a reduction in the flanker effect with practice, but only under limited circumstances and with distractors that carried task-relevant information (the flankers were predictive of the main target); these effects also seemed to be highly dependent on the particular parameters and timing of task, suggesting limited possibility for transfer. These studies are examples of the general trend in tasks that examine practice effects and attention: improvements are tied to the particular task-relevant stimuli and generally involve the development of automatic associations between stimuli and the correct response.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The contextual cueing paradigm (Chun and Jiang, 1998; 1999) leads to improved task performance because the distractors actually guide attention, rather than being filtered (though see Makovski, et al (2008), for an example of learning restricted to the target items). Brown and Fera (1994) showed a reduction in the flanker effect with practice, but only under limited circumstances and with distractors that carried task-relevant information (the flankers were predictive of the main target); these effects also seemed to be highly dependent on the particular parameters and timing of task, suggesting limited possibility for transfer. These studies are examples of the general trend in tasks that examine practice effects and attention: improvements are tied to the particular task-relevant stimuli and generally involve the development of automatic associations between stimuli and the correct response.…”
Section: Discussionmentioning
confidence: 95%
“…Here, the term “efficiency of selection” concerns the degree to which the deployment of selective visual attention to a target item can successfully exclude potentially distracting information from adjacent locations in the scene. Brown and Fera (1994) used a version of the flanker task first discussed by Eriksen and Eriksen (1974) to examine this question. The flanker task provides a direct measure of the efficiency of selective attention: interference by the flanking items indexes a failure to filter them in spite of their task-irrelevance.…”
Section: Introductionmentioning
confidence: 99%
“…This strategy might cause the concern that practice effects have led to an attenuation of the compatibility effects of the joint Simon and joint flanker task. However, previous studies have shown that spatial compatibility effects of the Simon task are quite resistant against practice effects (Dutta & Proctor, 1992), and compatibility effects of the flanker task are reasonably robust (Brown & Fera, 1994). Moreover, even if practice effects have been present, they should have affected both joint conditions-Simon and flanker-equally.…”
Section: Open Questions and Future Directionsmentioning
confidence: 91%
“…Therefore, it can be assumed that, compared to a wider spacing, late selection is involved more strongly in this case. For instance, target selection could rely more on categorical information than on metric spatial information (see also P. Brown & Fera, 1994;LaBerge & Brown, 1989). To see how early and late selection vary with spacing, we conducted a flanker task experiment where the participants had to categorize numerals as odd or even.…”
Section: Experiments 1: Spacing Between Target and Flankersmentioning
confidence: 99%
“…For an effective spatial filtering it is important that the filter can be positioned optimally at the target location. Accordingly, spatial uncertainty about the exact location of target and flankers usually leads to an impaired performance (e.g., P. Brown & Fera, 1994;Goolkasian & Bojko, 2001;Miller, 1991;Paquet & Lortie, 1990). Thus, it is reasonable to assume that under spatial uncertainty a reliable performance can be achieved only if response selection is strongly supported by a late stimulus selection stage, where selection is based, for instance, on categorical spatial information such as "the middle letter.…”
Section: Experiments 2: Spatial Uncertainty and Eccentricity Of The Stmentioning
confidence: 99%